Erbium-Doped Zirconia-Alumina Silica Glass-Based Fiber as a Saturable Absorber for High Repetition Rate Q-Switched All-Fiber Laser Generation *Supported by the Postgraduate Research of Malaysia under Grant No PG098-2014B, and the CSIR of Government of India. (August 2017) - Reddy, P. Harshavardhan; Kadir, N. A. A.; Paul, M. C.; Das, S.; Dhar, A.; Ismail, E. I.; Latiff, A. A.; Harun, S. W.
Abstract : We propose and demonstrate a Q-switched erbium-doped fiber laser (EDFL) using an erbium-doped zirconia-alumina silica glass-based fiber (Zr-EDF) as a saturable absorber. As a 16-cm-long Zr-EDF is incorporated into a ring EDFL cavity, a stable Q-switching pulse train operating at 1565 nm wavelength is successfully obtained. The repetition rate is tunable from 33.97 kHz to 71.23 kHz by increasing the pump power from the threshold of 26 mW to the maximum of 74 mW. The highest pulse energy of 26.67 nJ is obtained at the maximum pump power .